Tailoring the textural properties of hierarchical porous carbons using deep eutectic solvents. Issue 23 (26th May 2016) - López-Salas, N.; Carriazo, D.; Gutiérrez, M. C.; Ferrer, M. L.; Ania, C. O.; Rubio, F.; Tamayo, A.; Fierro, J. L. G.; del Monte, F.
Abstract : DESs containing resorcinol, urea and choline chloride allow the preparation of monolithic carbons with bicontinuous porous structures, the pore dimension of which can be easily tailored by the molar ratio of the components at the original DES. Abstract : Soft-template approaches have been frequently applied for the preparation of porous carbons. Most of these processes proved highly effective for the preparation of mesoporous carbons with pore diameters below 10 nm but less explored has been the preparation of carbons with mesopores larger than 10 nm. The lack of syntheses providing large and well-interconnected mesopores is by no means a trivial issue because it limits the achievement of materials suitable for applications where pore surface accessibility is crucial – e.g. electrodes in supercapacitors or adsorbents in flow-through systems, among others. In this work, we have used deep eutectic solvents (DESs, a sort of ionic liquid, that are obtained by complexation of quaternary ammonium salts with hydrogen-bond donors) composed of resorcinol, urea and choline chloride for the preparation – via formaldehyde polycondensation and subsequent carbonization – of hierarchical porous carbons with micropores and large mesopores within the 10 to 20 nm range. The formation of large mesopores took place at the polycondensation stage via a spinodal decomposition process where some components forming the DES acted as precursors of the polymer phase, while some other ones were segregated into a polymer depleted phase. Thus, the ultimate dimension of the mesopores was controlled by the mass ratio between the segregated and condensed phases, and this mass ratio by the molar ratio of the components forming the original DES. We have finally demonstrated that carbons with larger mesopores exhibited better performance as electrodes in supercapacitor cells.